Service factors influence on customer satisfaction in innovative e- commerce - SANKAR, DR. JEGANATHAN GOMATHI; MR. SURYA H (The journal of contemporary issues in business and government, 2020)
The research paper titled customer satisfaction in E-commerce industry. The objective of the study is to identify the factors that influencing customer satisfaction in E-commerce industry. Descriptive research is used in the study as the research design and the sampling method used is convenience sampling. The sample size of the study is 150 respondents and it is analyzed using SPSS tool. The collected data were classified, tabulated and analyzed with statistical tools such as frequency analysis and Regression analysis. It is found that factor affecting customer satisfaction are delivery problem, privacy and security, service recovery. Among the factors, Service recovery factor positively influences the customer satisfaction.